(untitled) (Perner’s Contacts, 2012)
Belt conveyors are machines used for transportation of packaged goods or bulk materials along horizontal and inclined paths. During operation of a belt conveyor, as in any human activity, unexpected and undesirable events may take place resulting in damage to human health or material loss. The analysis of these accidents contributes to understanding and proposal of measures suitable for reducing the risk as much as possible. The assessment of risks is not only a legal obligation but also a process of increasing safety at work.